Locke’s Legitimization and Appropriation of Property for Private Ownership - Haaga, Paul T.; Pilla, Joseph Genda (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The central argument of this paper rest on Locke’s property theory which is also referred to as the labour theory of appropriation. This theory according to Locke is rooted in natural law and it teaches that property comes about originally through the exercise of labour on natural resources. In line with Locke’s perspective, the paper argues that property would be that which a person takes from the common things of nature and mixes with his labour and therefrom, gains right of ownership over it; which is the labour theory of ownership or the principle of the first appropriation. Adopting an expository and analytic method, the paper raised fundamental issues such as: identifying the ‘self’ as one property that a person exclusively possesses, with which he can rightly appropriate from the common heritage and the fact that all inferior creatures, be common to all men, every man has property in his own person: this nobody has any right to but himself.” Exploring Locke’s idea, the paper presents a moral defence of the legitimacy of unilateral appropriation by connecting labour with the right of ownership. It further concludes that for Locke, when a person mixes her labour with any part of the common natural endowments, she gains the right of ownership over it.